Does Experience Exert Impact on a PPP Performance? - Joanna Wegrzyn (Institute of Economic Research (IER), 2017)
Researchers traditionally assume that learning is a product of experience. In general it means that learning can only take place through the attempt to solve a problem and therefore only takes place during activity (Arrow, 1962). On the ground of organizational theory it has two implications. First we can agree that repeated activity requires less effort. Second we can argue that firms undertake activities, with which they have been the most successful in the past and that they expect to be the most successful in the future. The aim of the research is twofold. Firstly, this article aims to investigate if we can identify a relationship between the experience in PPP projects and the performance of initiatives of this kind. Secondly, the article aims to provide an interpretation of the relationship between experience and PPP performance. This research investigates factors influencing the survival of PPP projects in Poland over the period 2009-2015. Cox proportional hazard model is utilized to distinguish between PPPs that succeeded to the operation phase and those that were cancelled on the procurement stage. The research confirms the existence of a positive relationship between experience in PPP and the outcome of a PPP development.
Keywords: C41; D01; H54; L32; O22; 330; survival analysis; public - private partnership (PPP); organizational learning; investment decisions